2019
DOI: 10.1101/19012013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial DNA copy number and incident heart failure: The Atherosclerosis Risk in Communities (ARIC) study

Abstract: Background: The association between mitochondrial DNA-copy number (mtDNA-CN) and incident heart failure (HF) in the general population is unclear. Methods: We examined the association between mtDNA-CN and the risk of incident HF among 10,802 participants free of HF at baseline from the Atherosclerosis Risk in Communities (ARIC) study, a large bi-racial population-based cohort. mtDNA-CN was estimated using probe intensities on the Affymetrix Genome-Wide Human single nucleotide polymorphisms Array 6.0. Incident … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
4
9
0
Order By: Relevance
“…This finding is consistent with a large body of work showing that mtDNA-CN measured in blood is associated with numerous aging-related phenotypes for which the primary tissue of interest is not blood (e.g. chronic kidney disease 13 , heart failure 11 , and diabetes 66 ). Also consistent with this finding is recent work demonstrating that mtDNA-CN measured in blood is associated with mtRNA expression across numerous non-blood tissues, suggesting a link between mitochondrial function measured in blood and other tissues 67 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is consistent with a large body of work showing that mtDNA-CN measured in blood is associated with numerous aging-related phenotypes for which the primary tissue of interest is not blood (e.g. chronic kidney disease 13 , heart failure 11 , and diabetes 66 ). Also consistent with this finding is recent work demonstrating that mtDNA-CN measured in blood is associated with mtRNA expression across numerous non-blood tissues, suggesting a link between mitochondrial function measured in blood and other tissues 67 .…”
Section: Discussionsupporting
confidence: 89%
“…The relative copy number of mtDNA (mtDNA-CN) has been shown to be positively correlated with oxidative stress 6 , energy reserves, and mitochondrial membrane potential 7 . As a minimally invasive proxy measure of mitochondrial dysfunction 8 , decreased mtDNA-CN measured in blood has been previously associated with aging-related disease states including frailty 9 , cardiovascular disease [10][11][12] , chronic kidney disease 13 , neurodegeneration 14,15 , and cancer 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the results found in our study, previous studies all showed that lower mtDNA-CN measured from peripheral blood was related to an increased risk of CVD (4)(5)(6)(7)(8)(9)(10)(11). The only prospective study that assessed the relationship between mtDNA content and either CAD or HF used the Atherosclerosis Risk in Communities (ARIC) Study (9,10).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the results found in our study, previous studies all showed that lower mtDNA-CN measured from peripheral blood was related to an increased risk of CVD (4-11). The only prospective study that assessed the relationship between mtDNA content and either CAD or HF used the Atherosclerosis Risk in Communities (ARIC) Study (9,10). In the ARIC study, composed of 20,163 participants (2460 incident CHD) with a mean follow-up of 13.5 years, a lower mtDNA-CN was associated with an increased risk of incident CHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation